AB0448 Baseline Characteristics and Changes in Disease Activity at 12 Months in Patients Treated with Abatacept Versus Other Biologic Disease-Modifying Antirheumatic Drugs in Clinical Practice Setting – Results from the Brass Registry. (9th June 2015) - Alemao, E.; Joo, S.; Frits, M.; Iannaccone, C.; Shadick, N.; Weinblatt, M.
Abstract : Background: The advent and use of biologic DMARDs (bDMARDs) have advanced the standard of care in RA, reducing unmet needs and increasing remission rates. Abatacept (ABA), a selective T-cell co-stimulatory modulator, is approved for the management of moderate-to-severe RA. In clinical trial settings, ABA showed efficacy similar to TNFi. 1 In clinical practice, TNFi are the predominantly used bDMARDs in the management of RA; however, there are limited data comparing ABA to bDMARDs in clinical practice. Objectives: The primary objective was to assess baseline characteristics of RA patients receiving ABA or other bDMARDs in clinical practice. The secondary objective was to evaluate changes from baseline to 12 months in RA disease activity measures (DAS28 [CRP], CDAI and SDAI), as well as patient-reported outcomes (PROs; physical functioning [modified Health Assessment Questionnaire (mHAQ)], quality of life [EQ-5D] and arthritis active/pain today) in RA patients receiving ABA or other bDMARDs in clinical practice. Methods: Data from patients enrolled in the Brigham and Women's Hospital Rheumatoid Arthritis Sequential Study (BRASS) registry, established in 2003, were analysed to address the study objectives. The registry comprises mostly patients with established RA who were evaluated annually on clinical measures and semi-annually on multiple clinical PROs and resource utilization parameters. The current analysis is based on patients who had exposure to bDMARDs and had data on at least one disease activity measure available during 12-month follow-up in the registry. Descriptive statistics were used to summarize the baseline differences in demographics, disease activity measures and laboratory measurements between RA-patients prescribed ABA vs other bDMARDs. Mean change from baseline to 12 months in disease activity measures and PROs were assessed using univariate and multivariate regression analyses that controlled for baseline covariates, including baseline ABA vs bDMARD treatments. Results: A total of 748 patients were included in the analysis; of these, 102 (13.6%) received ABA and 646 (86.4%) received other bDMARDs; the majority (83%) of ABA patients had prior exposure to bDMARDs. At baseline, ABA patients (vs other bDMARD patients) were older (mean [SD] age: 59.5 [10.7] vs 54.8 [14.2] yrs; p=0.0015), with higher CRP levels (17.09 [41.5] vs 8.1 [19.2] mg/L; p=0.0004), higher DAS28 (CRP) (4.42 [1.58] vs 3.68 [1.65]; p≤0.001), higher mHAQ (0.59 [0.52] vs 0.37 [0.47]; p≤0.001) and lower EQ-5D (0.71 [0.15] vs 0.80 [0.17]; p≤0.001). After controlling for baseline covariates, the mean changes from baseline to 12 months in disease activity measures and PROs were comparable in ABA and other bDMARD patients (Table ). Conclusions: RA patients prescribed abatacept (vs other bDMARDs) in clinical practice tend to be older, with longer disease duration, higher disease activity scores, higher acute-phase reactant and the majority had prior bDMARD exposure. Despite this, mean changes from baseline to 12 months in disease activity measures and PROs in patients on abatacept and other biologic therapies were comparable. References: Schiff M, et al. Ann Rheum Dis 2014;73:86–94. Disclosure of Interest: E. Alemao Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, S. Joo Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, M. Frits: None declared, C. Iannaccone: None declared, N. Shadick Grant/research support from: Bristol-Myers Squibb, Crescendo Bioscience, Amgen, UCB, AbbVie, M. Weinblatt Grant/research support from: Bristol-Myers Squibb, Crescendo Bioscience, UCB, Consultant for: Bristol-Myers Squibb, Crescendo Bioscience, UCB, Abbvie, Roche, Janssen, Pfizer, Lilly, Amgen